Compreender para intervir: um estudo sobre a prática alienativa nas varas de família - Silva, Cristina Martins Cunha da (2011)
This thesis is the product of our concerns about the significant repercussions caused by parental alienation, mainly the irreversible severing of the affective bond. The researcher recognizes that parental alienation is a social product that commonly is a part of the family dynamics occurring when couples separate. Mothers and fathers dissatisfied by the separation, use their minor children as an instrument to attack their ex husband‟s or wives‟ without considering that children are legally dependent and still developing. It was verified that this alienating practice is an interdisciplinary theme of legal interest (given that it emerges within the legal system and translates into a conflict of interests requiring state intervention) and therefore developing into a psychological conflict. Thus, from an interdisciplinary perspective the researcher seeks to understand the phenomena based on the experience and the work of judiciary psychologists who focus in the legal system (family court). The sample was derived from reports provided by these professionals and subsequently a transversal and qualitative study was conducted based on relevant literature. Testimonials from people who experienced the alienating process were also used, allowing us to observe the anxiety and suffering triggered by parental alienation. Throughout the study the researcher listed determining characteristics (such as unprocessed mourning), as well as, problems encountered by people involved in the context (for example, legal morosity). It should be noted that our analysis focused primarily on the child as a person whose personality is still developing. This fact pressures parents to accept responsibly their parental role in order to promote healthy emotional development of their children. Thus, throughout the study the researcher highlighted the need for parents to be mature, in order to distinguish between conjugal and parental responsibility, given that parental alienation has as a factor the need to differentiate between these two obligations. The researcher observed that the family dynamics carries with it peculiar characteristics requiring joint intervention of legal and psychological professional possessing special abilities in family mediation. In addition to jurisprudence that clearly states the role of the state psychotherapy is mentioned and family mediation are considered possible alternatives to assist in dealing with and promoting effective and operative restoration of social peace. The researcher also suggest that the afore mentioned professionals work with parents stressing the need to distinguish between parental and conjugal responsibility and that parents clearly understand that a child needs to live with both a father and a mother ( each one occupying effectively their parental function thus contributing to the full development of the child). Finally, the research suggests that only joint interdisciplinary cooperation of the professionals involved in an understanding that is broader than judicial norms is it possible to face and inhibit in a coherent and effective manner the existing alienating practice.